Ecosophy in Bhagavad Gita: Natural Harmony and Interdependence - Chalise, Keshav Raj (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2026)
This paper examines how the notion of ecosophy, a notion developed from the Western philosophy of the deep ecology, is inherent in the Eastern philosophy of Bhagavad Gita. Bhagavad Gita, a book on the philosophy of life, provides different notions of ecosophy such as harmony and interdependence. Harmony is the essence of life and existence. Western natural philosophy has talked much about natural harmony in the last three decades, especially with the deep ecological movement and the publication of Ecology, Community, and Lifestyle (1989), and The Dream of the Earth (1988). Western societies have realized that a change has to be taken in the way we treat nature for better harmony. As a result, the theory of ecosophy has been developed to redefine the human and nature relationship. But in the East, the idea of natural harmony can be traced back to ancient philosophical and religious traditions that emphasize the interconnectedness and balance of the natural world. The concept of harmony with nature has long been a central tenet in the texts like Vedas and Upanishads, however, the real principle of environmental awareness is a quite new issue to both the East and the West. This paper aims to unearth how Bhagavad Gita has focused on the essence of natural harmony. As a philosophical and spiritual dialogue set within the larger epic, the Mahabharata, Bhagavad Gita establishes a discussion on selflessness, devotion, self-discipline, meditation, and the nature of the soul, but this paper uses lately practiced Western theory of ecosophy as a tool to explore the idea of the state of balance, interconnectedness, coexistence and synchronicity in natural creation as enunciated in the dialogue between Krishna and Arjuna in Bhagavad Gita.